FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH KABUPATEN DAN KOTA DI PROVINSI SUMATERA SELATAN DAN PROVINSI LAMPUNG - LIS DJUNIAR; SUNARDI SUNARDI; DEWI SARI; EMAN SATRIA (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2021)
This study aimed at determining the influence of local govermnent characteristis and the results of BPK audit examininations on the performance of local govermnent in the regencies/cities of South Sumatera and Lampung Province. The type of this study was an associative researceh. The population in this study was 31 regencies/cities in the Provinces of South Sumatera and Lampung. The data used was secondary data in the from of LKPD in 2015-2017, so that 93 observations. The data collection method used in this study was documentation. The data analysis technique used was quantitative and qualitative. Data analysis technique used was multiple linear regression. The results showed that, the age of local government and the level of dependence on the central governments affected the financial performance of local governments, while prosperity, capital expenditure, and the results of BPK audit examinations did not affect the financial performance of local governments.